Effects of chronic exposure to Aspergillus fumigatus on epidermal growth factor receptor expression in the airway epithelial cells of asthmatic rats. (3rd July 2014) - Gao, Fu-Sheng; Cao, Tong-Mei; Gao, Yan-Yan; Liu, Mei-Juan; Liu, Yong-Quan; Wang, Ze
ABSTRACT: Epidemiologic studies suggest that increased concentrations of airborne spores of Aspergillus fumigatus closely relate to asthma aggravation. Chronic exposure to A. fumigatus aggravates airway inflammation, remodeling, and airway hyperresponsiveness in asthmatic rats. The effects of chronic exposure to A. fumigatus on epidermal growth factor receptor (EGFR) expression in the airway epithelial cells of asthmatic rats remain unclear. This study aimed to investigate the effects of chronic exposure to A. fumigatus on injury and shedding of airway epithelium, goblet cell metaplasia, and EGFR expression in the airway epithelial cells of asthmatic rats. A rat model of chronic asthma was established using ovalbumin (OVA) sensitization and challenge. Rats with chronic asthma were then exposed to long-term inhalation of spores of A. fumigatus, and the dynamic changes in injury and shedding of airway epithelium, goblet cell metaplasia, and EGFR expression were observed and analyzed. Chronic exposure to A. fumigatus could aggravate airway epithelial cell damage, upregulate the expression of EGFR and its ligands EGF and TGF-α, promote goblet cell metaplasia, and increase airway responsiveness in rats with asthma. Chronic exposure to A. fumigatus upregulates the expression of EGFR and its ligands in asthmatic rats. The EGFR pathway may play a role in asthma aggravation induced by exposure to A. fumigatus .